Persepsi Siswa Kelas X Terhadap Implementasi Kurikulum Merdeka Pada Pembelajaran Bahasa Indonesia Di SMK Putra Pertiwi - Dwi Norma Apriyanti; Hindun Hindun (Jurnal Pendidikan dan Sastra Inggris, 2024)
This study aims to determine the perceptions of grade X students towards the implementation of Merdeka Curriculum in Indonesian language learning at SMK Putra Pertiwi using a qualitative descriptive method. Data sources were obtained through observation and distributing questionnaires and then analyzed using a random sampling technique. The results of this study indicate that the perception of the implementation of the Merdeka Curriculum in Indonesian language learning at SMK Putra Pertiwi has gone well because it has received a positive response from grade X students